EFFECT OF DEPRESSION ON EMOTIONAL STABILITY OF HIGHER SECONDARY STUDENTS - Saxena, Pratima; Raizada, Viveka (International Journal of Psychosocial Rehabilitation, 2020)
The present study was carried out to find out the effect of Depression, Gender and Faculty on Emotional Stability of adolescent students. The study was conducted on a sample of 450 students (225 boys & 225 girls) of higher secondary students of Kanpur. The data were analyzed with the help of Three-way ANOVA followed by t- test. The result of study revealed that Students belonging to Science Faculty were found to have significantly better Emotional Stability than those of Arts and Commerce Faculty. Males were found have significantly higher Emotional Stable than Females. Emotional Stability of subjects belonging to different Depression levels was found to be similar. Emotional Stability of Males and Females belonging to different Faculties were found to be of same degree. Emotional Stability of Arts, Science and Commerce students belonging to different levels of Depression were found to be of same degree. Emotional Stability of Male and Female students belonging to different levels of Depression were found to be of same degree. Emotional Stability of Male and Female students belonging to different Faculties and levels of Depression were found to be of same degree. Thus, it shows that students belonging to Science Faculty were found to have significantly better Emotional Stability than those of Arts & Commerce Faculty. It might possible Science students thinks scientifically or practically thus could be more Emotional Stable. It was also found that Emotional Stability of Boys was higher than that of Girls. This might be because boys are generally more emotional stable than girls. But here Emotional stability at various Depression levels are found at par, it might possible that Depression levels i.e. High, Moderate or Low throws an equal impact on Emotional Stability.